The Influence of Leadership, Motivation and Work Environment on Employee Performance - Iwan Budiherwanto; Tri Nur Rohmah; Arif Triwinars; Icha Adelya Puspita Ningrum; Wulan Juliana (Journal of Economics and Public Health, 2026)
The purpose of this study is to examine the influence of leadership, motivation, and work environment on employee performance, both partially and multi-dimensionally. The sampling technique used was non-probability sampling with a simple sample type so that the research sample consisted of 64 respondents. Data collection used a questionnaire and was analyzed using descriptive and statistical analysis. Validity and reliability analysis were used for the questionnaire. regression analysis and determination test. The results of the study explain that leadership, motivation, and work environment have a significant influence between the variables of leadership, motivation, and work environment simultaneously on employee work performance, as well as partial testing of each variable of leadership, work environment has an influence on employee performance. Meanwhile, motivation has no influence on employee performance.